Kepemimpinan Kepala Sekolah Dalam Meningkatkan Kinerja Guru Selama Pandemi Covid-19 di Sekolah Dasar Negeri Uma Buntar Kabupaten Sumbawa - Risdianto, Rudi; Fahruddin, Fahruddin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The purpose of this study was to describe the principal's leadership in improving teacher performance at SDN UMA BUNTAR, Sumbawa Regency. This study uses a descriptive method with a qualitative approach. Data collection in the study was carried out by observation, documentation, and interviews. Informants in this study include: Principals and Teachers. The data analysis technique used in this study uses the Miles and Huberman interactive data analysis model. Which consists of four flow of activities, namely data collection, data reduction, data presentation and drawing conclusions or verification. To measure the validity of the data in this study, researchers used triangulation techniques. The triangulation used in this study is source triangulation using cross-checking of data between informants. The results showed that the principal's leadership in improving teacher performance during the COVID-19 pandemic at the State Elementary School of UMA BUNTAR, Sumbawa Regency was good.